Analysis of the actual electrical loads of public premises embedded in residential buildings - Yu. I. Soluyanov; A. I. Fedotov; A. R. Akhmetshin; V. I. Soluyanov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. With the help of data from smart electricity meters, an analysis of the profiles of electrical loads of commercial organizations that are part of apartment buildings was carried out. The results obtained are compared with their current standard values. New values of specific electrical loads for public premises are considered: pharmacies, grocery and manufactured goods stores, catering establishments, office premises.METHODS. Half-hour load profiles were obtained from intelligent electricity metering devices installed directly at the objects under study, data transmission was carried out by an automated electricity metering system. The observation intervals were several tens of days. To process the experimentally obtained data, statistical methods for the analysis of electrical loads were used.RESULTS. The article describes the relevance of the topic, presents the profiles of electrical loads of public premises with the highlighting of characteristic features separately for each group of electricity consumers. New specific design electrical loads are considered, including an analysis in comparison with existing standards.CONCLUSION. The calculated values of electrical power in order to ensure technological connection for public premises, including social and cultural facilities, must be updated, since today there is a significant difference between the actual and calculated according to regulatory documents electrical loads. Updating the specific design electrical loads of public premises will reduce the locked capacity of these facilities, at the same time reduce the cost of technological connection, thereby increasing the rating of the investment climate in the region.